"Triple low" free-breathing CTPA protocol for patients with dyspnoea. Issue 8 (August 2022) - Cantarinha, A.; Bassil, C.; Savignac, A.; Devilder, M.; Maxwell, F.; Crézé, M.; Purcell, Y.M.; Bellin, M.-F.; Meyrignac, O.; Dillenseger, J.-P.
Abstract : AIM: To assess the performance of a "triple-low" free-breathing protocol for computed tomography pulmonary angiography (CTPA) evaluated on patients with dyspnoea and suspected pulmonary embolism and discuss its application in routine clinical practice for the study of the pulmonary parenchyma and vasculature. MATERIAL AND METHODS: This study was conducted on a selected group of dyspnoeic patients referred for CTPA. The protocol was designed using fast free-breathing acquisition and a small, fixed volume (35 ml) of contrast agent in order to achieve a low-exposure dose. For each examination, radiodensity of the pulmonary trunk and ascending aorta, and the dose–length product (DLP) were recorded. A qualitative analysis was performed of pulmonary arterial enhancement and the pulmonary parenchyma. RESULTS: This study included 134 patients. Contrast enhancement of the pulmonary arteries (409 ± 159 HU) was systematically >250 HU. The duration of acquisition ranged from 0.9 to 1.3 seconds for free-breathing imaging. The mean DLP was in the range of low-dose chest CT acquisitions (145 ± 73 mGy·cm). The analysis was deemed optimal in 90% (120/134) of cases for the pulmonary parenchyma. Sixty-nine per cent (92/134) of cases demonstrated homogeneous enhancement of the pulmonary arteries to the subsegmental level. Only 6% (8/134) of examinations were considered uninterpretable. CONCLUSION: The present "triple-low" CTPA protocol allows convenient analysis of the pulmonary parenchyma and arteries without hindrance by respiratory motion artefacts in dyspnoeic patients. Highlights: CT pulmonary angiograms can now be performed without breath-hold. Free-breath CTPA protocol is efficient for dyspnoeic patients. CTPA can be obtained with 35ml of iodinated contrast agent. kVp adaptation is now a rule that permits acquisition of low dose CTPA.